(untitled) (Research, Society and Development, 2020)
Bee pollen is a product of bees that has gained attention for its nutritional and functional characteristics. The characteristics of this product vary depending on several factors with emphasis on vegetation where bee hives are inserted. Thus, this work aimed to evaluate nutritional quality of pollen from caatinga and apply it in development of cakes. For this, pollen samples were collected from hives located in caatinga, passing through stages of selection of raw material; drying at temperatures from 40 ° C to 60 ° C for 21 days; Picking up foreign matter; and Grinding. In the sample of flour produced, analyzes of moisture, proteins, ash, lipids, fibers and carbohydrates were performed. Then the flour was applied in cake formulations in proportions of 0, 10, 20 and 30% replacement of wheat flour. After preparation, formulations were subjected to microbiological analysis of Coliform at 45 ° C and Salmonella sp., and analyzed sensorially by the researchers. In the end it can be concluded that the drying condition was not sufficient to adapt pollen to the legislation. It was also noticed that pollen lipid content in the Northeast is higher than that recorded for the south of Brasil. Regarding application in preparation of cakes, it can be concluded that enrichment interferes by darkening the cake and making it softer. It is recommended that in subsequent researches the sensory analysis be carried out in order to ratify the observed factors.